Pemberdayaan Masyarakat Melalui Edukasi Pencegahan Stunting di Kelurahan Kemanisan, Kecamatan Curug, Kota Serang - Yusransyah; Sofi Nurmay Stiani; Baha Udin; Resi Yulianti; Salsa Putri Fatimah Az-zahra; Desi Permatasari (LPPM Universitas Langlangbuana, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth and cognitive development. This community service activity aimed to empower the community through stunting prevention education in Kemanisan Village, Curug District, Serang City. The method used was health education accompanied by an evaluation using a questionnaire. The activity involved 26 respondents, all of whom were female. The results showed that the respondents’ average knowledge score was 6.42, with knowledge categorized as moderate (57.7%), good (19.2%), and poor (23.1%). The highest proportion of correct responses was found in the question regarding the role of integrated health service posts (Posyandu) in stunting prevention (88.5%), while the lowest was related to knowledge of nutritional supplements (26.9%). The education provided was able to improve community understanding of stunting; however, further education is needed, particularly regarding the use of nutritional supplements and family-based prevention strategies.